The impact of systemic inflammatory markers on survival in metastatic gastric cancer patients receiving first-line chemotherapy (Annals of Medical Research, 2021)
Aim: The prognostic impact of elevated systemic inflammatory tools, including the neutrophil-lymphocyte ratio (NLR) and the platelet-lymphocyte ratio (PLR), remains moot in cancer patients. This research was performed to explore the predictive worth of these markers for prognoses in metastatic gastric cancer (mGC) patients receiving chemotherapy.Material and Methods: We retrospectively appraised 158 patients diagnosed with mGC between February 2009 and November 2017. According to threshold values that were identified by receiver operating characteristic (ROC) curve analysis, the NLR and PLR were each divided into two groups: ≤ 2.11 and >2.11, ≤ 158.8, and >158.8, respectively. The Cox proportional hazards model was applied to uncover the probable predictors of progression-free survival (PFS) and overall survival (OS).Results: According to univariate analysis, poor performance status, high NLR, high PLR, and anemia were significantly correlated with inferior OS receiving first-line palliative chemotherapy. High NLR, high PLR, and anemia were significantly correlated with poor PFS. In the multiple analysis, an elevated NLR was identified to be an independent predictor of inferior OS (OR: 2.70, 95% CI: 1.75-4.16, p0.001) and PFS (OR: 1.47, 95% CI: 1.00-2.17, p=0.047). Additionally, anemia was independent prognostic factors for the OS (OR: 0.69, 95% CI: 0.47-0.99, p=0.046).Conclusion: Findings of this research revealed that NLR was an independent prognostic tool of PFS and OS in mGC patients undergoing first-line chemotherapy.Keywords: Metastatic gastric cancer; neutrophil to lymphocyte ratio; platelet-to-lymphocyte ratio; prognosis.
Keywords: Metastatic gastric cancer; neutrophil to lymphocyte ratio; platelet-to-lymphocyte ratio; prognosis.